Simple and Reproducible Derivatization with Benzoyl Chloride: Improvement of Sensitivity for Multiple Lipid Classes in RP-UHPLC/MS - Peterka, Ondřej; Jirásko, Robert; Vaňková, Zuzana; Chocholoušková, Michaela; Wolrab, Denise; Kulhánek, Jiří; Bureš, Filip; Holčapek, Michal (American Chemical Society, 2021)
The chemical derivatization of multiple lipid classes was developed using benzoyl chloride as a nonhazardous derivatization agent at ambient conditions. The derivatization procedure was optimized with standards for 4 nonpolar and 8 polar lipid classes and measured by reversed-phase ultrahighperformance liquid chromatography-tandem mass spectrometry. The derivatization and nonderivatization approaches were compared on the basis of the calibration curves of 22 internal standards from 12 lipid classes. The new method decreased the limit of detection 9-fold for monoacylglycerols (0.9-1.0 nmol/mL), 6.5-fold for sphingoid base (0.2 nmol/mL), and 3-fold for diacylglycerols (0.9 nmol/mL). The sensitivity expressed by the ratio of calibration slopes was increased 2- to 10-fold for almost all investigated lipid classes and even more than 100-fold for monoacylglycerols. Moreover, the benzoylation reaction produces a more stable derivative of cholesterol in comparison to the easily in-source fragmented nonderivatized form and enabled the detection of fatty acids in a positive ion mode, which does not require polarity switching as for the nonderivatized form. The intralaboratory comparison with an additional operator without previous derivatization experiences shows the simplicity, robustness, and reproducibility. The stability of the derivatives was determined by periodical measurements during a one month period and five freeze/thaw cycles. The fully optimized derivatization method was applied to human plasma, which allows the detection of 169 lipid species from 11 lipid classes using the high confidence level of identification in reversed-phase (RP)-ultra high performance liquid chromatography (UHPLC)/mass spectrometry (MS). Generally, we detected more lipid species for monoacylglycerols, diacylglycerols, and sphingoid bases in comparison with previously reported papers without the derivatization.
Jednoduchá a reprodukovatelná derivatizace benzoylchloridem: Zlepšení citlivosti pro více lipidových tříd v RP-UHPLC/MS
Keywords: performance liquid-chromatography; mass-spectrometry; relative quantification; high-throughput; phospholipids; enhancement; cholesterol; platform; disease; blood; vysokoúčinná kapalinová chromatografie; hmotnostní spektrometrie, relativní kvantifikace; vysoká propustnost; fosfolipidy; zlepšení; cholesterol; platforma; nemoc; krev